CONTRIBUTION OF THE BOARDING PROGRAM TOWARDS THE FORMATION OF THE ISLAMIC CHARACTER OF STUDENTS OF MAN 3 KEBUMEN - Arina Salsabila; Ahmad Khoiri; Vava Imam Agus Faisal3 (Alphateach (Jurnal Profesi Kependidikan dan Keguruan), 2026)
Islamic character formation is one of the main essences of a system. This goal is aimed at producing a balanced generation, not only intellectually superior but also morally superior, based on Islamic law. One way to support this character formation is the boarding school program. This study aims to describe the implementation of the boarding school program, analyze its contribution to the formation of students' Islamic character, and identify factors that support and hinder its implementation at MAN 3 Kebumen. This study used a qualitative approach with descriptive methods. Data were collected through interviews, observations, and documentation involving a boarding school supervisor and nine students. Data analysis was conducted using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The research results show that the boarding school program is implemented through various structured and sustainable activities, such as congregational prayer, tahajud (night prayer), Quran reading, memorization (tahfidz), studying the Yellow Book, and cultivating Islamic behavior in daily life. The boarding school program makes a positive contribution to the development of students' religious character, discipline, responsibility, independence, and social awareness. The success of this program is based on the exemplary leadership of the instructors, the religious environment, a well-structured program, and school support. Factors hindering its success include a lack of discipline on the part of some students, peer influence, differences in background, and limited student housing. Therefore, the boarding school program makes a positive contribution to the development of students' Islamic character.